Anti-HIV and Anticandidal Properties of Punica granatum L. (Pomegranate): A Pharmacological Agent for the Oral Cavity - Maira Huerta-Reyes; Luis A. Gaitán-Cepeda; Luis O. Sánchez-Vargas (New Advances in Medicine and Medical Science Vol. 1, 2023)
Pomegranate (Punica granatum) trees have long been used extensively in traditional medicine to treat a wide range of illnesses, including dental and oral diseases. The most frequent clinical manifestation in HIV patients is caused by Candida albicans, which has been demonstrated to have strong anticandidal effects in recent years. Since the oral cavity is crucial from diagnosis to adherence to HAART therapy in HIV/AIDS population, the present review offers a general overview of up-to-date knowledge of the chemical composition and anti-HIV and anticandidal properties of the plant species P. granatum involved in the oral cavity in order to collaborate in the development of novel anti-HIV agents that will be useful in future clinical practice. The literature reviewed revealed that crude extracts of pomegranate and its main compounds isolated, and in particular, anthocyanins and gallotannins possess inhibitory activity on different HIV-targets, including binding viral proteins and the 3 replicative HIV-enzymes. Pomegranate also demonstrated anticandidal effects on 10 different species in the literature that was reviewed. Consequently, pomegranate seems to be a great candidate to investigate and incorporate into the treatment of the oral cavity in HIV/AIDS patients, in that in addition to its dual-pharmacological effects such as antiviral and anticandidal, pomegranate represents an easily accessible inexpensive and safe natural source, with a wide range of oral pharmaceutical forms.